2008
DOI: 10.1021/bi800002j
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Cross-Seeding: An Approach To Explore Protein Aggregates In Living Cells

Abstract: Protein aggregation is associated with the pathology of many diseases, especially neurodegenerative diseases. A variety of structurally polymorphic aggregates or preaggregates including amyloid fibrils is accessible to any aggregating protein. Preaggregates are now believed to be the toxic culprits in pathologies rather than mature aggregates. Although clearly valuable, understanding the mechanism of formation and the structural characteristics of these prefibrillar species is currently lacking. We report here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Indeed, it has been reported that, following IPTG deprivation, protein expression is strongly inhibited in T7-based inducible strains, like the one employed here [45]. Thus, after IPTG removal we monitored growth rates and normalized them with respect to that of the wild type, to allow for the effect of overexpression-related cellular stress.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been reported that, following IPTG deprivation, protein expression is strongly inhibited in T7-based inducible strains, like the one employed here [45]. Thus, after IPTG removal we monitored growth rates and normalized them with respect to that of the wild type, to allow for the effect of overexpression-related cellular stress.…”
Section: Resultsmentioning
confidence: 99%
“…Both in vitro and in E. coli the aggregation prone P39A CRABP variant seeds early oligomer formation while polyQ tracts with lengths above the pathological threshold seeded the formation of later, detergent resistant aggregates. 888,889 Thus, as observed for polyQs appended to other folded proteins, 890893 the context of the polyQ sequence is key. Aggregation of polyQ repeats tagged with an FP, (often cerulean fluorescent protein (CFP), GFP, or yellow fluorescent protein (YFP) at the C-terminal end) or complementary GFP fragments has been studied in yeast cells, in mammalian cells and in the transparent nematode C. elegans (for reviews and methods see refs (852, 894, and 895)).…”
Section: Theoretical and Experimental Methods To Study Idpsmentioning
confidence: 96%
“…However, this view has recently been challenged by the observation of efficient cross-polymerization between several non-prion amyloid species (Yagi et al, 2005; Han, Weinreb & Lansbury, 1995; Westermark, Lundmark & Westermark, 2009; Morales et al, 2010; O’Nuallain et al, 2004; Ma & Nussinov, 2012). Seeds formed from amyloid fibers of some non-homologous proteins can either reduce or eliminate the lag-time of amyloid formation of another protein, (Yagi et al, 2005; Han, Weinreb & Lansbury, 1995; Westermark, Lundmark & Westermark, 2009; Morales et al, 2010; O’Nuallain et al, 2004; MacPhee & Dobson, 2000) although the phenomenon is not universal and even single point mutations have been shown to disrupt cross-seeding in some cases (O’Nuallain et al, 2004; Jarrett & Lansbury, 1992; Hinz, Gierasch & Ignatova, 2008; Rajan et al, 2001). Cross-seeding may also be asymmetric, with one protein able to seed another but not be seeded by it (Yu et al, 2012; Siddiqua et al, 2012).…”
Section: Introductionmentioning
confidence: 99%